A REVIEW ON UPGRADING METHODOLOGY USED IN PRESTRESSED CONCRETE BEAMS (International Journal of Food and Nutritional Sciences, 2023)
This study explores recent advancements in prestressed concrete beams, focusing on innovative techniques, materials, and design methodologies. The analysis encompasses the structural performance, durability, and sustainability aspects of these advancements, shedding light on their implications for the construction industry. The findings contribute to a deeper understanding of how prestressed concrete technology continues to evolve, offering enhanced efficiency and resilience in infrastructure projects. This research delves into the contemporary developments in prestressed concrete beams, elucidating novel methodologies, materials, and design approaches. Through a comprehensive examination of structural integrity, durability, and environmental sustainability, this study highlights the transformative impact of recent innovations on the realm of construction. The insights derived contribute to a nuanced comprehension of the evolving landscape of prestressed concrete, unveiling its progressive strides towards heightened effectiveness and resilience in modern infrastructure. This study reviews recent advancements in prestressed concrete beams, analyzing innovations in materials, construction techniques, and design methodologies. The research emphasizes improvements in structural performance, durability, and sustainability, offering insights into the evolving landscape of prestressed concrete technology. The findings contribute to the ongoing dialogue in civil engineering, providing valuable information for practitioners and researchers aiming to enhance the efficiency and longevity of infrastructure projects.